Pengaruh Kepemimpinan Kepala Sekolah Dan Budaya Sekolah Terhadap Kepuasan Kerja Guru SMA Swasta - Dimas Auzan Rahman; Unifah Rosyidi; Fakhrudin Arbah (Program Studi Manajemen Pendidikan, 2023)
Based on basic education data (DAPODIK) at the high school level in Bekasi Regency in the Odd Semester of the 2022/2023 Academic Year, the number of students of 44 public high schools in Bekasi Regency reached 45,043 students. This means that as many as 77.85% of students attend public high schools. While the number of students attending private high schools is only around 12,811 students (22.15%). As a result, as many as 60 private high schools were declared unhealthy/unhealthy, due to a shortage of students. If this continues, it is likely that in the following year, many private high schools in Bekasi Regency will close because they do not get students. Of course, this must be overcome with a strategy to improve the quality of schools, one of which is to improve the performance of private high school teachers through job satisfaction. The purpose of this study was to determine the influence of the principal's leadership and school culture on the job satisfaction of private high school teachers in Bakasi District. This study used a quantitative approach with an explanatory method with a population of all private high school teachers in Bekasi Regency totaling 848 people. Data was collected using questionnaires and analyzed using path analysis. The results of the pathway analysis showed that there was a positive influence of the principal's leadership on teacher job satisfaction. The percentage of influence contribution is 37.5%. This means that the magnitude of the influence of the principal leadership variable (X1) on teacher job satisfaction (Y) is 37.5%. The results of the pathway analysis show that there is a positive influence of school culture on teacher job satisfaction. The percentage of influence contribution is 43.7%. This means that the magnitude of the influence of school culture variables (X2) on teacher job satisfaction (Y) is 43.7%.